2020
DOI: 10.22289/2446-922x.v6n2a4
|View full text |Cite
|
Sign up to set email alerts
|

FATORES DE MOTIVAÇÃO DE PRATICANTES DE EXERCÍCIO FÍSICO DA CIDADE DE PETROLINA-PE: um estudo comparativo

Abstract: Este estudo analisou os fatores motivacionais de 203 praticantes de exercício físico na cidade de Petrolina-PE. Os instrumentos utilizados foram o Inventário de Motivação do Exercício-2 (EMI-2) e um questionário com perguntas sobre sexo, idade, estado civil, renda mensal, tipo de exercício, tempo de prática e frequência semanal de prática. A análise dos dados foi realizada pelos testes "U" de Mann-Whitney e Kruskal-Wallis (p <0,05). Os resultados mostraram que os homens apresentaram escores mais altos nos fato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…In the study by Batista et al [12], 203 exercise practitioners were analyzed to identify the main adherence factors for training. Thus, the study identified that sociodemographic aspects influence adherence to physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Batista et al [12], 203 exercise practitioners were analyzed to identify the main adherence factors for training. Thus, the study identified that sociodemographic aspects influence adherence to physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…When related to the practice of physical exercise, motivation goes through physiological, psychological, social, affiliation, power, achievement, incentives, rewards, and difficulties factors that complement different factors, such as disease prevention, physical conditioning, weight control, appearance, stress control, entertainment, health rehabilitation, competition, and social recognition 10 . Thus, the motivation to practice physical exercise is reflected in the quality of life (QOL) since it involves self-esteem, social, family, psychological, and personal well-being, economic power, acquisition, and autonomy in the day's tasks, and can be improved through regular physical exercise 11,12 .…”
Section: Introductionmentioning
confidence: 99%